2007
DOI: 10.1007/s10616-007-9097-9
|View full text |Cite
|
Sign up to set email alerts
|

Porcine platelet lysate as a supplement for animal cell culture

Abstract: A novel supplementation of cell growth media based on a porcine platelet lysate was developed for culture of animal-derived cells. The platelet lysate was produced from porcine blood and contained lysate of platelets and plasma components. It showed satisfactory microbiological integrity and it carried only low amount of endotoxins (<10 EU/mL). The porcine platelet lysate supported well proliferation of Vero (African green monkey transformed kidney epithelial cells), Chinese hamster ovary (CHO) and hybridoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
6
0
3
Order By: Relevance
“…Anna et al in 2007 and Lohmann et al in 2010 added PL to the cell culture media and the results showed that PL had good potential to support cell culturing and proliferation [22,23]. Pazoki et al in 2014 also used PL in pre-antral follicle culture medium for the first time and the result demonstrated that PL has an acceptable effect on oocyte growth [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Anna et al in 2007 and Lohmann et al in 2010 added PL to the cell culture media and the results showed that PL had good potential to support cell culturing and proliferation [22,23]. Pazoki et al in 2014 also used PL in pre-antral follicle culture medium for the first time and the result demonstrated that PL has an acceptable effect on oocyte growth [24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is some evidence that growth factors, cytokines, IGF and EGF can affect maturation and follicle development [27,28]. In recent years, some studies have been conducted to improve the culture medium by adding different supplements like PL [22][23][24]. In this study, the maturation medium was enriched by different concentration of PL and maturation, fertilization and subsequent development were monitored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tais preocupações, impulsionaram diversos pesquisadores a buscar alternativas aos componentes de origem animal empregados nesses métodos, focando suas atenções principalmente sobre o Soro Fetal Bovino, por ser este uma fonte de nutrientes, presente no meio de cultura de vários tipos celulares (Aldén et al, 2007).…”
Section: Introductionunclassified